Improving Students' Speaking Ability Using Time Token Arends in the Eleventh Grade of SMAN 1 Mataram - Alfiqar, M. Rangga Sahid; Amin, Muhammad; Susanti, Ni Wayan Mira; Amrullah (Journal of English Education Forum (JEEF), 2025)
Speaking, as a critical component of language acquisition, is often hindered by factors such as low confidence, limited vocabulary, and reluctance to use English in class. This research investigates the effectiveness of the Time Token Arends (TTA) cooperative learning strategy in enhancing the speaking ability of eleventh-grade students at SMAN 1 Mataram.  Through Classroom Action Research (CAR), this study was conducted over two cycles involving 21 students. The instruments used included speaking tests, observations, and questionnaires, with the speaking tests focusing on pronunciation, grammar, vocabulary, and fluency. The results demonstrated a significant improvement in students’ speaking performance—from a pre-test average of 52.14 to a post-test cycle I average of 71.42 and finally to 82.61 in cycle II. Additionally, 95.23% of students achieved the minimum mastery criterion after the second cycle. The findings suggest that TTA is an effective and engaging strategy to boost students' speaking fluency and confidence. The research implies valuable insights for teachers seeking innovative methods to encourage active language use and equitable participation in speaking activities.